MENGURAI KEBEKUAN HUBUNGAN AGAMA DAN SAINS MELALUI PEMAHAMAN SAINTIFIC METHOD PERSPEKTIF IAN G. BARBOUR - Luthfiyah Luthfiyah (Universitas Muhammadiyah Ponorogo, 2019)
The study is begun from discuss about four typology between religion and science Ian G. Barbour, including with independence, conflict, dialog and integration. Where two first types are related with character each other, while two last types emphasized to seek the similarity and how they can be united each other. Afterwards, in connection religion and science, Barbour emphasized to comprehension to the saintific method. Including with experience and interpretation, interaction between experiment and theory, how the theory is formed and the criteria of its evaluation which empty into the understanding as the purpose of science. In the meantime, there are four ideologies wich considered differently a theory until different in its position. They are positivism, instrumentalism, realism and idealism. As the closing in this study is emphasise the benefit of science to humanity life.